2003
DOI: 10.1021/ol034469l
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective Synthesis of Piperazines by Manganese-Mediated Reductive Cyclization

Abstract: A simple and effective synthesis of trans aryl-substituted piperazines using a Brønsted acid and manganese(0) is described. [reaction: see text]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…With respect to PCET coupling of imine derivatives, Sigman has reported the synthesis of piperazines by the reductive coupling of bisimines with a combination of Brønsted acids and elemental manganese as a one–electron reductant (Scheme 54) [258]. The authors found that the success of the reaction correlated with the acidity of the Brønsted acid additive, consistent with a PCET process.…”
Section: Ketones and Carbonyl Derivativesmentioning
confidence: 99%
“…With respect to PCET coupling of imine derivatives, Sigman has reported the synthesis of piperazines by the reductive coupling of bisimines with a combination of Brønsted acids and elemental manganese as a one–electron reductant (Scheme 54) [258]. The authors found that the success of the reaction correlated with the acidity of the Brønsted acid additive, consistent with a PCET process.…”
Section: Ketones and Carbonyl Derivativesmentioning
confidence: 99%
“…[18] The two C–C bonds in the ring are created in the same transformation, as opposed to traditional piperazine syntheses, based on multistep sequences of cyclization and reduction reactions (ketopiperazine,[20] pyrazine reduction[21] or intramolecular aza-pinacol coupling). [22] Using the best combination of these methods, a piperazine product like 3 a (see Table 1) would take no less than four steps in the making (even longer for more elaborated substituents or unsymmetrical analogs),[22a, 23] thus discouraging its exploration in catalysis.…”
mentioning
confidence: 99%
“…For example, 3a was quantitatively transformed into the corresponding piperazine 4a as a single isomer (Table 3, entry 1). [18] A bicyclic piperazine derivative was also obtained from 3b in 98 % yield (Table 3, entry 2). [19] However, attempts to obtain a seven-membered ring were unsuccessful and resulted in oligomerization (Table 3, entry 3).…”
Section: Resultsmentioning
confidence: 99%